2012
DOI: 10.1177/0733464812454007
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospitalization in a National Sample of Medicare Home Health Care Patients

Abstract: Acute care hospitalization during or immediately following a Medicare home health care (HHC) episode is a major adverse outcome, but little has been published about HHC patient-level risk factors for hospitalization. We determined risk factors at HHC admission associated with subsequent acute care hospitalization in a nationally representative Medicare patient sample (n=374,123). Hospitalization was measured using Medicare claims data; risk factors were measured using Outcome Assessment and Information Set dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 29 publications
4
58
5
Order By: Relevance
“…Several studies have reported that low BADL was associated with hospitalization or death . In the current study, we did not find an association between BADL and poor prognosis.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Several studies have reported that low BADL was associated with hospitalization or death . In the current study, we did not find an association between BADL and poor prognosis.…”
Section: Discussioncontrasting
confidence: 86%
“…Several studies have reported that low BADL was associated with hospitalization or death. [16][17][18][19][20][21] In the current study, we did not find an association between BADL and poor prognosis. Because ONEHOME participants were skewed to very low BADL, this might have obscured the significance of BADL as a factor.…”
Section: Discussioncontrasting
confidence: 51%
“…16 Studies of the causes of rehospitalization reveal inconsistent patterns of risk factors for rehospitalizations in the home health care setting. 79 Due to the complex nature of HF, evaluating individual risk factors for rehospitalization in isolation may limit the ability of clinicians to optimally target health services such as telehomecare, which is a remote monitoring intervention used in the home health care setting. Instead, understanding associations among risk factors for rehospitalization using the standardized home health care electronic health records for Medicare recipients (i.e., the Outcome and Assessment Information Set (OASIS), which may be elucidated using data mining techniques, may provide guidance for admission assessments by home health care clinicians to help target those patients most likely to benefit from telehomecare, or who may need additional interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have utilized the OASIS as administrative data to discover risk factors for hospitalization, 7,9,14,15 and two studies have used data mining techniques to evaluate the OASIS data set. 16,17 However, to our knowledge, no studies have applied these approaches to the OASIS-C version that was initiated in 2010, which we obtained from a large home health care company to identify risk factors for rehospitalization among telehomecare patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the study was heart failure patients due to their increased risk of hospital readmission from a home care setting (24,25), and therefore the importance to nurses. The results of the study were used to design a prototype dashboard, focusing on tracking and monitoring of patient information (weight and vital signs) over time.…”
mentioning
confidence: 99%